A pragmatic randomized controlled trial of a cardiac hospital-to-home transitional care program in a Singapore academic medical center. Issue 2 (April 2020) - Chen, Yanying; Tan, Yi Jin; Sun, Ya; Chua, Cheng Zhan; Yoo, Jeffrey Kwang Sui; Wong, Shing Hei; Chen, Helen; Meng Wong, John Chee; Phan, Phillip
Background: Rehospitalizations are common in healthcare. They are costly for hospitals and patients and a substantial percentage are preventable, partly because hospital-to-community transitions are often unmanaged or poorly managed. In this study, we conducted a pragmatic randomized, controlled trial to evaluate the effectiveness of a new nurse–practitioner-led transitional care program called CareHub, piloted in Singapore's National University Hospital. Methods: Study population included all eligible cardiac patients admitted between July 2016 and November 2016. Patients were followed for six months post-discharge. Primary outcomes other than emergency department visits were all cardiac-related: number of readmissions, specialist visits, emergency department visits, and total days readmitted. Secondary outcomes: variables related to quality of life and transitional care. Regression analyses were used to estimate the intent-to-treat effect of CareHub and explore treatment heterogeneity. Results: CareHub reduced the mean number of unplanned readmissions by 0.23 (a 39% reduction relative to control mean of 0.60 unplanned readmissions, p  < 0.05), mean number of all readmissions by 0.20 (31% reduction relative to control mean of 0.63 readmissions, p  = 0.10), mean number of total unplanned days in hospital by 2.2 (56% reduction relative to control mean of 4.0 days, p  < 0.05), mean number of total days in hospital by 2.0 (42% reduction relative to control mean of 4.3 days, p  < 0.10). Treatment effects varied by pre-admission health and socio-economic status. Conclusion: A carefully designed protocolized cardiac hospital-to-home transition program can reduce resource utilization while improving quality of life.